Estratégias eficazes para otimização da operação de mineração de bauxita em Juruti : análise de carregamento e transporte de minério e remoção de estéril - Newton Flávio dos Santos Oliveira (2023)
This dissertation explores the challenges faced by the bauxite mining operation in Juruti, which has been experiencing cost increases due to changes in the physical characteristics of the mine. The study aims to seek viable alternatives to make the mining operation in Juruti more efficient and sustainable. The study proposes methodologies for loading and transporting ore and removing waste rock, with fleet sizing and cost modeling performed to compare them with the current operation. The results demonstrate that the proposed methodologies significantly reduce mining costs in Juruti, with a potential 65% reduction in operational costs. The study finds that there is a greater potential for cost reduction in removing waste rock, with gains 150% larger than those of ore loading and transport. The results suggest that the proposed alternatives present a feasible and effective solution to improve the economic and environmental performance of mining in Juruti. Moreover, the results provide a solid foundation for future discussions and developments of mining methodologies for tabular bauxite deposits in the Amazon. The study concludes that the proposed methodologies can contribute to the advancement of sustainable mining in the region, promoting greater economic and environmental efficiency in mining activities.